Spiritual care and support from the perspective of hospitalized cancer patients - Juškauskienė, Erika; Spirgienė, Lina; Riklikienė, Olga (Slauga. Mokslas ir praktika, 2021)
The aim was to describe the experience of non-terminal patients with oncological disease about the spiritual care and support provided to them in the nursing and supportive care hospital. Methods. The study was conducted in 2018 in four Lithuanian nursing and supportive care hospitals. During the face-to-face interviews, 118 patients with non-terminal oncological diseases shared their experiences on the spiritual care and support provided in the health care institution. Purposive sample selection was applied. The answers were analyzed by the method of qualitative inductive thematic content analysis. Kaunas Regional Bioethics Committee (No. BE-2-84) issued the permission to conduct the research. Findings. Patients with oncological diseases, in describing the spiritual care and support they received in nursing and supportive care hospital, associated it primarily with the sacraments and religious rituals provided by clergy or their assistants. Patients identified clergy and spiritual advisors, also medical, nursing and social care staff, and relatives as the main providers of spirtiual care. Patients expressed a desire to receive the spiritual help and support from a multidisciplinary team whose members liaise with each other, coordinate their actions, and together seek the best solutions. One third of patients experienced that their spiritual needs and expectations left without due attention or were not met at all. Some patients felt that there was too little spiritual support and help in the hospital. Conclusions. Patients with oncological diseases, in describing the spiritual care and support they received in nursing and supportive care hospital, associated it primarily with the sacraments and religious rituals provided by clergy or their assistants and to lesser extent with conversation and communication initiated by medical staff. The spiritual needs of patients with oncological diseases must become an integral part of holistic patient care not only at the theoretical level but also in clinical practice.